An analysis of the impact of financialisation on commodity futures and spot prices - Calitz, Geoffrey George (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The debate on the commodity financialisation phenomenon was triggered in response to the steep rise in commodity futures and spot prices during the 2000-2011 super cycle. The two schools of thought regarding the underlying causes of such dramatic price increases are divided between those attributing the super cycle to fundamental drivers, and those who suggest that fundamental drivers alone are an insufficient explanation, and that other non-fundamental drivers are important. Fundamental drivers commonly cited in the literature include the sustained growth in demand for commodities throughout the early 2000s from emerging economies, such as China and India, and shocks to supply chains such as crop failures, export bans, and other factors such as macroeconomic dynamics. However, an alternative school of thought found empirical evidence which suggested that in addition to fundamental drivers, non-fundamental drivers such as key regulatory changes in commodity and financial markets in 1999/2000, and the subsequent changes to the trading activities in commodity derivative markets and the resultant historic growth in the participation of purely financial investors, significantly impacted the structure and price dynamics in commodity markets, in a phenomenon known as the financialisation of commodity markets. This study contributes to the empirical literature by expanding compared with previous studies the time period under investigation, as well as expanding the range of commodities examined. The most recent 2020-2024 period of rising prices is included, and the behavior of both cross-sector and same-sector pairwise return correlations of futures and spot prices in this period is compared to the pre-financialisation period. The study contributes to the literature by examining how the cross market and cross asset return correlation structure has behaved throughout the entire post-financialisation era. The study makes a further contribution by establishing the statistical significance of futures market returns as a predictor of spot market returns. It is found that the financialisation phenomenon impacted both commodity futures and spot markets. Pairwise return correlation is substantially greater throughout Period 2 (post-financialisation) compared to Period 1 (pre-financialisation) for same-sector and cross-sector pairs of futures and spot prices. The structural change in return correlation between these two periods was found to be especially pronounced for cross-sector pairs of futures and spot prices. The financialisation hypothesis is further supported by the findings of persistent structural changes in cross market and cross asset return correlation, which has become even more pronounced in the later stages of financialisation. The most recent period of rising commodity prices, Period 2(c) (2020-2024), is found to show elevated pairwise return correlation for futures and spot prices levels when compared to Period 1 (pre-financialisation), but the increase in correlations is less than in earlier financialisation periods such as Period 2(a) (2000-2011) and Period 2(b) (2012-2019). These findings suggest that index buying may be less important in the later stages of commodity financialisation. It was found that futures market returns are statistically significant predictors of spot market returns. Furthermore, the causal effect of futures market returns on spot market returns under the effect of financialisation (2000-2024) is found to be statistically significant in all five examples (WTI crude oil, gold, silver, LME copper and aluminium) examined in the study. The study finds that a clear structural change occurred in commodity spot and futures markets in the post-financialisation period. The consistency of this structural change is evident when analysing both cross sector and same sector pairwise return correlation behavior of commodity spot and futures prices, and when analysing cross market and cross asset return correlation between commodity markets and financial market benchmarks. The implication for investors is that commodity markets no longer offer certain portfolio diversification benefits and downside protection to drops in equity markets previously found in the empirical literature, and investors need to recalibrate strategies to account for these structural changes. The study concludes that the commodity market financialisation hypothesis is sound, and this implies that further research is required to better understand the impact of such structural changes on commodity futures and spot markets. In addition, because futures market returns are found to be a statistically significant predictor of spot market returns, it is imperative that further research be undertaken which investigates the explicit relationship between futures and spot markets so that policy makers and market regulators better understand the links between these two markets so that policy decisions are better informed. Furthermore, it is necessary that future research investigates how the transmission of information occurs between futures and spot markets, and how this matters for consumers, and addresses what welfare implications may be associated with this. Lastly, the author has advocated for increased transparency and restrictions in commodity markets, suggesting that all trading occurs on open regulated exchanges and that position limits are implemented, so as to prevent any market distortion which may come from institutional speculators taking excessively powerful and large positions.
Keywords: Commodity price; Commodity futures -- Prices; Spot prices; Financialization; Commodities exchange; Commodity supercycle